Academic Senate Minutes 2004-12-16 - Academic Senate:::::::::
Chair Report. President Report. Fire Emergency Debrief. Expedited Revision: Hutchins BA approved for consent calendar. Expedited: Counseling MA approved for consent calendar. Expedited: Early Childhood Studies approved for consent calendar. Provost Report. Revision: Philosophy BA approved for consent calendar. Revision: Music Education, in Instrumental Jazz Track approved for consent calendar. Expedited: SOCI Major+Minor approved for consent calendar. Discontinuance: ECON Concentrations approved as a business item. Senate agenda approved.